Implementasi Algoritme SPECK Block Cipher dan Shamir's Secret Sharing Pada File Teks - Novita Krisma Diarti; Ari Kusyanti; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Formal letter is one example of processing important data that contains text files, therefore security is needed to protect the file. Security in files aimed so that only certain people can access the contents of the file. Encryption is one of technique to secure file in cryptography. Cryptography has many algorithms that can be used for encryption process. In this study, two algorithms in cryptography use to secure file, called SPECK block cipher algorithm and Shamir's secret sharing. SPECK block cipher algorithm is used for data encryption and decryption, while Shamir's secret sharing algorithm is used to share confidential data on files. Both algorithms are used to protect text files in order to maintain data security from irresponsible people. Testing involves three file sizes, such as size 4 KB with contents 3, 8, and 13 lines. Results show average of 9.433 s, 91.938 s, and 619.036 s respectively for mentioned file contents. Average results of CPU usage are 7.058%, 25.855% and 31.095% respectively for mentioned file contents. Lastly, average results of the amount of RAM usage are 377.277 MB, 414.283 MB, 440.231 MB respectively for each file contents.